Private Sector Development in Iraq : An Investment Climate Reform Agenda - Dabidian, Hooman; Stone, Andrew (World Bank, Washington, DC, 2014)
Despite decades of war and instability, Iraq's abundant natural resources, strategic geographic location and cultural history endow it with tremendous potential for growth and diverse economic development. Driven by windfall oil revenues in recent years the Government of Iraq (GoI) has invested heavily in rebuilding infrastructure with abundant oil reserves ensuring steady progress. However, decades of socialist policies have tightly bound Iraq's economy to the state. The private sector has had little opportunity or incentive to invest, operate efficiently or expand. Moreover, Iraq's conflicts have led to pervasive insecurity, an exodus of educated and skilled Iraqis, isolation from global networks of information and trade, and major damage to infrastructure.